The mediating role of environmental knowledge in the effect of environmentally sensitive thoughts and behaviors on business performance: practice in turkey - Durmaz, Yakup; Fidanog, Ahmet (Elsevıer Scı Ltd)
This research aims to investigate the mediating effect of environmental knowledge level on the effect of environmentally sensitive thoughts and behaviors on business performance. In the globalizing world, manufacturing enterprises are at the forefront in terms of their damage to the environment. It was conducted using the survey method on industrial enterprises operating in the organized industrial zone. The data obtained in the study were analyzed using the partial least squares structural equation modeling (PLS-SEM) method. In the research, it is seen that environmentally sensitive thoughts and behaviors have a positive and significant effect on the environmental performance of enterprises. It has been observed that environmental knowledge has a mediating effect on the effect of environmentally sensitive thoughts and behavior on the environmental performance of enterprises. Environmentally sensitive thoughts and behaviors of manufacturing business managers will have a positive impact on the environmental performance of enterprises. It has been determined that the environmental performance of enterprises is mediated by the environmental information of managers. The research provides information about the impact of environmentally sensitive thoughts and behaviors on the environmental performance of the enterprise to industrial and industrial enterprise managers. As a designed model, it is expected to contribute to the literature.
Keywords: Environmental thinking; Environmental behavior; Environmental information; Environmental performance; Manufacturing enterprises